ANALISIS DAN PERANCANGAN SISTEM DIGITAL BRANDING UMKM BERBASIS WEB DALAM MEMBANTU PROMOSI DAN PEMASARAN PRODUK - Indra Kurniawan; Yasa Maulana; Muhammad Sulthony; Ahmad Mubais; Nur Hikmah; Via Fitriana Putri; Zeni Kurniati (Journal of Information System and Computer, 2022)
The need for fast, precise and accurate information is currently important. Fulfillment of these information needs is carried out with the help of technology, especially in the field of computerization, such as in the field of the internet. In supporting the performance of UMKM, technological product innovation is needed to be developed and implemented, such as internet technology. Promotions carried out using internet technology are known as digital branding. Digital Branding plays an important role in the development of the use of information technology to provide information. The Waterfall model is one of the SDLC models that is often used in the development of information systems or software. This model uses a systematic and sequential approach. The use of the web in delivering information can make it easier to access information about UMKM anywhere and anytime online. Making it easier for UMKM products to be widely known.